Difficulties that Women Raising Children Face While Balancing Family Life with a Career - Bielskytė, Kristina; Smilgienė, Jurgita (Jaunųjų mokslininkų darbai, 2016)
Family life-career balance is an important issue for everyone, but mostly for women raising children. The stereotype that woman should give up work for the sake of her family predominates in society. Analysis of scientific and methodological literature showed that the following factors make it difficult to balance family life with a career: 1) conflicts between professional and personal life; 2) career interruption; 3) inflexible childcare services; 4) gender roles (gender discrimination); 5) employer attitude towards women of childbearing age.Aim of the research: to investigate what difficulties women raising children face while  balancing family life with a career. Data were collected via a semi-structured interview. Content analysis was done, the obtained data were interpreted. Purposive sampling was used (5 women who raise children and are balancing family life with a career). The results of empirical research showed that the main problem is conflicts between professional and personal life. Such conflicts arise because of a lack of time, a lack of employer understanding, household routine. Women withdraw from the labour market and lose social and professional skills. Equally shared parenting and housework is a good way to successfully manage personal and professional life. The respondents emphasized that the issue should be addressed by state policy.
Keywords: career and family; women raising children